2003
DOI: 10.1111/j.1365-2621.2003.tb09630.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Grapefruit Juice for Bitterness Removal by Amberlite IR 120 and Amberlite IR 400 and Alginate Entrapped Naringinase Enzyme

Abstract: Treatment of grapefruit (Citrus aurantium) juice with Amberlite IR 400 resulted in 69.23% naringin removal after 5 min exposure with significant clarification and 89.41% tartness (acidity) reduction. Amberlite IR 120 removed only 9% naringin in 1 min with increased shelf life of the juice without any change in clarity, quality, and naringin content. Alginate entrapped naringinase treatment of the juice resulted in 83.84% naringin hydrolysis at 55 °C and 220 rpm in 180 min with 1.98 enzyme units/mL of juice. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
27
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 16 publications
6
27
0
Order By: Relevance
“…The results were encouraging considering the beads could be used successively for three runs (9 h) with 24.4 % tannin removal. Enzymatic treatments of fruit juices to reduce haze and bitterness have been reported by various authors (2, 3, 10) . Reports on application of tannase in fruit juice processing are rare and there is no report of tannin removal from aonla juice which has a very strong astringency due to tannins.…”
Section: Resultsmentioning
confidence: 99%
“…The results were encouraging considering the beads could be used successively for three runs (9 h) with 24.4 % tannin removal. Enzymatic treatments of fruit juices to reduce haze and bitterness have been reported by various authors (2, 3, 10) . Reports on application of tannase in fruit juice processing are rare and there is no report of tannin removal from aonla juice which has a very strong astringency due to tannins.…”
Section: Resultsmentioning
confidence: 99%
“…There was no correlation between the pore volume of the adsorbents and oil loss values, while with higher surface areas, the oil loss enhanced. In literature, very diverse values for these material properties were reported for different amberlites, zeolites, sepiolites and montmorillonites . The data presented in Table provides the most common surface and pore properties of the adsorbent materials used in this study to observe their differences.…”
Section: Resultsmentioning
confidence: 99%
“…The best adsorption was achieved with amberlite XAD‐7, and adsorption of sugars and pigments were very low. In another study, bitterness removal from grapefruit juice with amberlites IR120 and IR400, and entrapped naringinase enzyme were compared. It was shown that IR400 reduced 69.23% of naringin, while reduction with IR120 was only 9%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…, 1996); laccase and adsorbent resin (Ritter & Dietrich, 1996), amberlite XAD‐7 resin in orange juice (Ribeiro et al. , 2002); amberlite IR‐400 and naringinase enzyme in grapefruit juice (Mishra & Kar, 2003); AcC in peach juice (Carabasa et al. , 1998); XAD‐16 resin in red grapefruit juice concentrate (Lee & Kim, 2003).…”
Section: Introductionmentioning
confidence: 99%